PENGARUH FREKUENSI DAN PERIODE PEMBERIAN PAKAN TERHADAP EFISIENSI PENGGUNAAN ENERGI METABOLISME AYAM BURAS SUPER - A., SETIAWAN; SUPRIJATNA, E.; MAHFUDZ, L.D. (Majalah Ilmiah Peternakan; Vol 20 No 3 (2017): Vol 20, No 3 (2017)DO - 10.24843/MIP.2017.v20.i03.p05, 2017)
This study was aimed to determine the appropriate feeding frequnce and feeding periods on crossbred native chicken for better efficiency in metbolisme energi utilization. Thestudy used 252 one day oldunsex crossbred native chickens with the average of initial body weight was 37.88 ± 1.89 g (CV = 5.02%) as materi. Comercial feed used in this study. Experiment used Split Plot Design with 3 levels of feeding frequency as main plot F1 (once), F2(2 times), F3(3 times) and 3 levels of feeding times periode as sub plot (P1start at 04:00 AM) P2 = start at 06:00 AM, P3 = start at 08:00 AM) with 4 replications that were arrange 36 experimental units, each unit wasconsisted of 7 chickens. Data were analyzed using analysis of variance and F-test at 5% level. The results showed that there was no effect (P>0,05)of interaction between feeding frequence and feeding periods or each factor on crossbred native chicken efficiency in metabilisme energi utilization, so that combination of F1P3 (once feeding frequence with 14 hours of feeding periods a day) most efficience for aplicates.